Wroxeter, the Cornovii and the Urban Process. Volume 2 - White, R. H. (Archaeopress, 2013)
In the mid-1990s, the site of the Roman city of Viroconium Cornoviorum at Wroxeter, Shropshire, was subjected to intensive geophysical survey. This volume reports on the archaeological interpretation of this work, marrying the geophysical data with a detailed analysis of the existing aerial photographic record created by Arnold Baker 1950s-1980s.